Development of an Atomic Level Model for BiFeO3 from First-Principles - Graf, Mónica Elisabet (2014)
We develop a first-principles atomistic shell model for BiFeO3 to study its ferroelectric and structural properties at finite temperature. The parameters of the potential are adjusted to reproduce first-principles results in different relevant configurations. Molecular dynamics simulations show that the resulting model is able to describe the ground-state ferroelectric R3c structure which remains stable as the temperature increases. At about 1100 K, system displays a first-order phase transition to the paraelectric Pbnm phase. Our results indicate that the developed model captures the delicate structural behavior shown by the ab-initio calculations and is able to reproduce the temperature behavior observed in experiments.